Modelling the spectral characteristics of 1.5 – 1.6 μm high-power asymmetric-waveguide single-mode laser diodes. (September 2018) - Kurnosov, V.D.; Kurnosov, K.V.
Abstract: Spectral characteristics of high-power single-mode laser diodes with a radiation wavelength of 1.5 – 1.6 μm are simulated with allowance for nonlinear losses. A satisfactory agreement between the calculation and experimental results as applied to the dependence of the wavelength and radiation spectrum width on the laser pump current is demonstrated. The effect of thermal resistance of a laser diode on the active region heating, spectrum width, and radiation wavelength is considered.